Preparation method and application of coconut shell carbon and transition metal bifunctional catalyst

A coconut shell carbon transition metal bifunctional catalyst, doped with nitrogen and sulfur, addresses the inefficiency of traditional zinc-air batteries by combining ORR and OER functions, improving the battery's performance and stability.

CN119181811AActive Publication Date: 2024-12-24HAINAN UNIV

Patent Information

Application Number
CN202411204420.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-24
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Traditional zinc-air batteries are limited by the need for two different catalysts for the anodic redox reaction (Oxygen Reduction Reaction, ORR) and cathode oxidation reaction (Oxygen Evolution Reaction), leading to low energy conversion efficiency, and the scarcity and high cost of platinum-based catalysts hinder commercialization.

Method used

A method is developed to prepare a coconut shell carbon transition metal bifunctional catalyst by doping with nitrogen and sulfur, combined with a nickel-cobalt-iron layered double hydroxide catalyst, creating a NiCoFe/NSC bifunctional catalyst that performs both ORR and OER functions.

Benefits of technology

The catalyst achieves excellent electrochemical performance and cycle stability when assembled into a zinc-air battery, enhancing the battery's charge and discharge efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181811A_ABST
    Figure CN119181811A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a coconut shell carbon and transition metal bifunctional catalyst. The preparation method comprises the following steps: S1, carbonizing and graphenizing coconut shells to obtain graphenized coconut shell carbon; s2, doping the graphene coconut shell carbon with nitrogen and sulfur to obtain nitrogen and sulfur doped graphene coconut shell carbon; s3, preparing a nickel-cobalt-iron LDH catalyst through a hydrothermal method; and S4, combining the nitrogen-sulfur doped graphene coconut shell carbon with a nickel-cobalt-iron LDH catalyst through a water-phase ultrasonic method to prepare the NiCoFe / NSC bifunctional catalyst. The coconut shell carbon and transition metal bifunctional catalyst is applied to the zinc-air battery as a cathode electrocatalyst material, and the electrochemical performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of fuel cell cathode electrocatalyst preparation, and in particular to a preparation method and application of a coconut shell carbon transition metal bifunctional catalyst. Background Art

[0002] Traditional fossil energy sources face challenges such as insufficient natural reserves, low conversion efficiency, and toxic byproduct pollution. The search for renewable energy sources with sufficient reserves, high conversion efficiency, and environmental friendliness has become a mainstream research direction. Zinc-air batteries have attracted widespread attention from researchers due to their high theoretical energy density, abundant and inexpensive raw materials, and safety and stability. The efficiency and cycle life of zinc-air batteries are limited by electrocatalysts. The traditional anodic redox reaction (Oxygen Reduction Reaction, ORR) and cathode oxidation reaction (Oxygen Evolution Reaction, OER) require two different catalysts to promote each, resulting in low energy conversion efficiency. Researching an electrocatalyst that simultaneously performs both ORR and OER functions is crucial for improving the efficiency of zinc-air batteries.

[0003] Nowadays, the widely used Pt / C catalyst has become a serious obstacle to the commercialization of fuel cells due to its defects such as material scarcity, high cost, poor stability, and easy poisoning. Therefore, in recent years, seeking and preparing non-precious metal catalysts with high performance, low cost, stability and anti-toxicity has become one of the hot research topics of scientific researchers. At present, non-precious metal catalysts are mainly divided into two categories, one is transition metal-nitrogen-carbon catalysts, and the other is non-metallic heteroatom-doped carbon catalysts. Transition metal-nitrogen-carbon materials face huge preparation challenges: (1) Transition metals will condense into particles under high temperature conditions, thereby reducing the intrinsic activity and number density of active sites; (2) The collapse of the carbon material structure and the large amount of amorphous carbon will cause a reduction in specific surface area and insufficient conductivity. At present, the key indicator for measuring powder bifunctional catalysts is the oxygen evolution reaction at a current density of 10mA / cm 2 The difference between the potential at the time of reaction and the half-wave potential of oxygen reduction, △E, is of great significance for the development of non-precious metal bifunctional electrocatalysts for oxygen evolution reaction and oxygen reduction reaction.

[0004] Therefore, it is of great significance to develop a non-precious metal catalyst with low cost, excellent performance, good stability and good toxicity resistance to replace Pt / C catalyst for zinc-air batteries through material selection and optimization of preparation methods. Summary of the Invention

[0005] In response to at least one defect or improvement need in the prior art, the present invention proposes a method for preparing a coconut shell carbon transition metal bifunctional catalyst and its application, the purpose of which is to construct a high-performance and stable transition metal-based catalyst to further improve the electrochemical performance of zinc-air battery cathode materials.

[0006] The technical solution of the present invention is achieved as follows:

[0007] A method for preparing a coconut shell carbon transition metal bifunctional catalyst comprises the following steps:

[0008] S1. Preparation of graphene-coconut shell carbon

[0009] Carbonize the coconut shell, mix it with concentrated sulfuric acid in an ice-water bath, add potassium permanganate until the solution turns brown, react in a water bath at 30-40°C, add hydrogen peroxide until the solution turns light golden yellow, let it stand, remove the supernatant, add hydrochloric acid solution and mix well, centrifuge, remove the supernatant, wash, and freeze-dry to obtain graphene coconut shell carbon;

[0010] S2, Graphene-based Coconut Shell Carbon Doped with Nitrogen and Sulfur

[0011] The graphene-doped coconut shell carbon is dispersed in a solvent, silicon dioxide is added, and the solvent is removed by ultrasonication to obtain a solid. The solid is mixed with a nitrogen-containing compound and a sulfur-containing compound, ground, calcined under an inert gas atmosphere, immersed in a strong acid, centrifuged and washed, and dried to obtain nitrogen- and sulfur-doped graphene-doped coconut shell carbon.

[0012] S3. Hydrothermal preparation of nickel-cobalt-iron LDH catalyst

[0013] Mix nickel chloride, cobalt chloride, ferric chloride and water to obtain a metal solution A; mix sodium carbonate with water to obtain an alkaline solution B; mix A and B evenly, react at 100-150° C. for 15-20 hours, cool, centrifuge, wash, and dry to obtain a nickel-cobalt-iron LDH catalyst;

[0014] Preparation of S4 and NiCoFe / NSC bifunctional catalysts

[0015] The nitrogen-sulfur doped graphene coconut shell carbon in S2 and the nickel-cobalt-iron LDH catalyst in S3 were mixed in water, ultrasonicated, centrifuged and washed, and dried to obtain a coconut shell carbon transition metal bifunctional catalyst, which was recorded as NiCoFe / NSC.

[0016] Preferably, the molar ratio of nickel chloride, cobalt chloride and ferric chloride in S3 is 1:4-8:1-5; the molar number of Fe accounts for less than 50% of the total molar number of Ni, Co and Fe.

[0017] Preferably, the coconut shell carbonization in S1 is specifically to dry the coconut shell, crush it, and place it in a tube furnace for carbonization under an argon atmosphere at 600°C; the concentration of the hydrochloric acid solution is 5wt%; and the freeze-drying is specifically to first freeze it at -5 to -20°C for 5-8h, and then freeze-dry it at -60 to -45°C for 36-42h.

[0018] Preferably, the solvent in S2 is 98-99.8 vol% ethanol, and the silica is hydrophilic nano-silica; the mass ratio of the graphene coconut shell carbon to the hydrophilic nano-silica is 1:5; the method for removing the solvent is to perform secondary rotary evaporation under normal pressure and low pressure conditions, the normal pressure rotary evaporation temperature is 70-80°C, the low pressure is 0.09 MPa, and the low pressure rotary evaporation temperature is 55-60°C; the strong acid is hydrofluoric acid.

[0019] Preferably, the inert gas in S2 is nitrogen, the nitrogen-containing compound is melamine, and the sulfur-containing compound is dibenzyl disulfide; the molar ratio of the solid, melamine, and dibenzyl disulfide is 6:5:5; the tubular furnace is heated to 300°C, maintained for 10 minutes, and then heated to 900°C, and heated at 900°C for 1 hour, and the heating rate is 5°C / min.

[0020] Preferably, the centrifugal washing is firstly washed with deionized water for 2 to 4 times, and then washed with anhydrous ethanol for 2 to 4 times, and the rotation speed of the centrifugal washing is 3000-4000 rad / min.

[0021] Preferably, the mass ratio of nitrogen-sulfur doped graphene coconut shell carbon to nickel-cobalt-iron LDH catalyst in S4 is 1:1.

[0022] The present invention also provides a coconut shell carbon transition metal bifunctional catalyst prepared by the preparation method.

[0023] The present invention also provides the use of the coconut shell carbon transition metal bifunctional catalyst prepared by the preparation method in a zinc-air battery.

[0024] The present invention also provides a zinc-air battery, in which the anode is a zinc sheet and the cathode is an air electrode. The air electrode includes a diaphragm, nickel foam, carbon paper coated with the coconut shell carbon transition metal bifunctional catalyst prepared by the above preparation method, and an air diffusion layer.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention involves doping graphene coconut shell carbon with nitrogen and sulfur to obtain nitrogen- and sulfur-doped graphene coconut shell carbon, and combining the nitrogen- and sulfur-doped graphene coconut shell carbon with a nickel-cobalt-iron LDH (layered double hydroxide) catalyst prepared by a hydrothermal method through an aqueous phase ultrasonic method to obtain a nitrogen- and sulfur-doped graphene coconut shell carbon-loaded nickel-cobalt-iron LDH bifunctional catalyst, namely, a NiCoFe / NSC bifunctional catalyst. The catalyst realizes OER / ORR bifunctionality and has relatively excellent electrochemical performance. The coconut shell carbon transition metal bifunctional catalyst (nitrogen- and sulfur-doped graphene coconut shell carbon-loaded nickel-cobalt-iron LDH bifunctional catalyst) prepared by the present invention is assembled into a zinc-air battery, which has excellent charge and discharge cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the OER polarization curve of the coconut shell carbon transition metal bifunctional catalyst prepared in Examples 1-3 of the present invention.

[0028] Figure 2 The ORR polarization curves of the coconut shell carbon transition metal bifunctional catalysts prepared in Examples 1-3 of the present invention and Comparative Example 1 are shown.

[0029] Figure 3 The coconut shell carbon transition metal bifunctional catalyst prepared in Example 1 of the present invention is used in zinc-air batteries at 10 mA cm -2 The charge-discharge cycle stability. DETAILED DESCRIPTION

[0030] In order to better understand the technical content of the present invention, specific examples are provided below to further illustrate the present invention.

[0031] Unless otherwise specified, the experimental methods used in the examples of the present invention are all conventional methods.

[0032] Unless otherwise specified, the materials, reagents, etc. used in the examples of the present invention can be obtained from commercial sources.

[0033] Example 1

[0034] A method for preparing a coconut shell carbon transition metal bifunctional catalyst comprises the following steps:

[0035] S1. Preparation of graphene-coconut shell carbon

[0036] S1.1. Collect enough coconut shells, remove the coconut meat, crush the coconut shells into pieces, dry them at 80°C for 24 hours, crush the dried coconut shells, and sieve them to obtain particles with a 100-mesh sieve;

[0037] S1.2. Place the pellets prepared in S1.1 into a tube furnace and carbonize them at 600°C in an argon atmosphere for 2.5 h to obtain a preliminary coconut shell carbon sample.

[0038] S1.3. Stir 5 g of coconut shell carbon with 115 ml of concentrated sulfuric acid in an ice-water bath. Add potassium permanganate until the solution turns brown. Remove the ice-water bath and incubate in a water bath at 35 ± 5 °C for 8 h.

[0039] S1.4. Add 750 ml of deionized water intermittently and stir for 10 minutes. Then add 25 ml of hydrogen peroxide and stir until the solution turns light golden yellow.

[0040] S1.5. The solution in S1.4 was allowed to stand for 10 h, the supernatant was removed, and 200 ml of 5 wt% hydrochloric acid solution was added, mixed evenly, and centrifuged. After centrifugation, the supernatant was removed and an appropriate amount of deionized water was added for washing. After repeated several times, the remaining solution was poured into a Petri dish and frozen at -10°C for 5 h. The sample was then transferred to a freeze drying oven at -50°C and freeze-dried for 36 h to obtain a graphene-type coconut shell carbon sample.

[0041] S2, Graphene-based Coconut Shell Carbon Doped with Nitrogen and Sulfur

[0042] S2.1. Ultrasonic dispersion of 0.1 g of graphene-coconut shell carbon in 500 ml of 98 vol% ethanol. Add 0.5 g of hydrophilic nano-SiO2 (15 nm) and sonicate thoroughly. Then, remove the ethanol by rotary evaporation at atmospheric pressure (80°C) and 0.09 MPa (55°C) to obtain a flaky solid, which is then dried in an oven at 80°C.

[0043] S2.2. Mix 0.6 g of the flaky solid obtained in S2.1 with 0.5 g of melamine and 0.5 g of dibenzyl disulfide, and grind them. Place the resulting mixture in a tube furnace and heat it to 300°C under a nitrogen atmosphere, hold for 10 min, then heat it to 900°C and heat at 900°C for 1 h at a heating rate of 5°C / min.

[0044] S2.3. Soak the product obtained after heating in S2.2 in 50 mL of hydrofluoric acid for 24 h to remove silica, and then centrifuge to remove residual hydrofluoric acid. The centrifugal washing is performed by first washing with deionized water three times and then washing with anhydrous ethanol three times at a speed of 3000 rad / min. The obtained product is placed in a vacuum drying oven and dried at 80°C for 8 h to obtain nitrogen-sulfur doped graphene coconut shell carbon.

[0045] S3. Hydrothermal preparation of nickel-cobalt-iron LDH catalyst

[0046] S3.1. Mix nickel chloride, cobalt chloride, and ferric chloride in a molar ratio of 1:6:3 (8 mmol total) in a 50 ml beaker. Dissolve in 20 ml of ultrapure water to prepare a 0.4 mol / L mixed metal solution A.

[0047] S3.2. Weigh 5.299 g of Na2CO3 (500 mmol) using weighing paper and place it in a 50 ml beaker. Dissolve it in a small amount of water and transfer it to a 50 ml volumetric flask to make a 1 mol / L solution B.

[0048] S3.3. Use a pipette to transfer 20 ml of solution A and 16 ml of solution B into a 100 ml beaker and stir vigorously for 0.5 hours. Transfer the stirred liquid to a 50 ml reactor and react at 100°C for 20 hours. When cooled to room temperature, centrifuge and wash the product. Centrifuge washing is performed by washing with deionized water three times and then with anhydrous ethanol three times at a speed of 4000 rad / min. Then, dry at 80°C to obtain a powdered nickel-cobalt-iron LDH (layered double hydroxide) catalyst.

[0049] Preparation of S4 and NiCoFe / NSC bifunctional catalysts

[0050] S4.1 Take 0.5 g of nitrogen-sulfur doped graphene coconut shell carbon in S2.3 and 0.5 g of nickel-cobalt-iron LDH catalyst in S3.2 in a ratio of 1:1 and mix them in ultrapure water. Ultrasonicate for 2 h at room temperature with an ultrasonic power of 230 W. Centrifuge and wash the product. Centrifuge washing is to wash it 3 times with deionized water and then 3 times with anhydrous ethanol. The speed of centrifugal washing is 4000 rad / min. Then dry it at 80 ° C to obtain coconut shell carbon transition metal bifunctional catalyst (nitrogen-sulfur doped graphene coconut shell carbon loaded nickel-cobalt-iron LDH bifunctional catalyst, denoted as Ni 0.1 Co 0.6 Fe 0.3 / NSC bifunctional catalyst).

[0051] Example 2

[0052] A method for preparing a coconut shell carbon transition metal bifunctional catalyst comprises the following steps:

[0053] S1. Preparation of graphene-coconut shell carbon

[0054] S1.1. Collect enough coconut shells, remove the coconut meat, crush the coconut shells into pieces, dry them at 80°C for 24 hours, crush the dried coconut shells, and sieve them to obtain particles with a 100-mesh sieve;

[0055] S1.2. Place the pellets prepared in S1.1 into a tube furnace and carbonize them at 600°C in an argon atmosphere for 2.5 h to obtain a preliminary coconut shell carbon sample.

[0056] S1.3. Stir 5 g of coconut shell carbon with 115 ml of concentrated sulfuric acid in an ice-water bath. Add potassium permanganate until the solution turns brown. Remove the ice-water bath and incubate in a water bath at 35 ± 5 °C for 8 h.

[0057] S1.4. Add 750 ml of deionized water intermittently and stir for 10 minutes. Then add 25 ml of hydrogen peroxide and stir until the solution turns light golden yellow.

[0058] S1.5. The solution in S1.4 was allowed to stand for 10 h, the supernatant was removed, and 200 ml of 5 wt% hydrochloric acid solution was added, mixed evenly, and centrifuged. After centrifugation, the supernatant was removed and an appropriate amount of deionized water was added for washing. After repeated multiple times, the remaining solution was poured into a Petri dish and frozen at -5°C for 8 h. The sample was then transferred to a freeze drying oven at -60°C and freeze-dried for 36 h to obtain a graphene-type coconut shell carbon sample.

[0059] S2, Graphene-based Coconut Shell Carbon Doped with Nitrogen and Sulfur

[0060] S2.1. Ultrasonic dispersion of 0.1 g of graphene-coconut shell carbon in 500 ml of 98 vol% ethanol. Add 0.5 g of hydrophilic nano-SiO2 (15 nm) and sonicate thoroughly. Then, remove the ethanol by rotary evaporation at atmospheric pressure (80°C) and 0.09 MPa (55°C) to obtain a flaky solid, which is then dried in an oven at 80°C.

[0061] S2.2. Mix 0.6 g of the flaky solid obtained in S2.1 with 0.5 g of melamine and 0.5 g of dibenzyl disulfide, and grind them. Place the resulting mixture in a tube furnace and heat it to 300°C under a nitrogen atmosphere, hold for 10 min, then heat it to 900°C and heat at 900°C for 1 h at a heating rate of 5°C / min.

[0062] S2.3. Soak the product obtained after heating in S2.2 in 50 mL of hydrofluoric acid for 24 h to remove silica, and then centrifuge to remove residual hydrofluoric acid. The centrifugal washing is performed by first washing with deionized water three times and then washing with anhydrous ethanol three times at a speed of 3000 rad / min. The obtained product is placed in a vacuum drying oven and dried at 80°C for 12 h to obtain nitrogen-sulfur doped graphene coconut shell carbon.

[0063] S3. Hydrothermal preparation of nickel-cobalt-iron LDH catalyst

[0064] S3.1. Mix nickel chloride, cobalt chloride, and ferric chloride in a molar ratio of 1:4:5 (8 mmol total) in a 50 ml beaker. Dissolve in 20 ml of ultrapure water to prepare a 0.4 mol / L mixed metal solution A.

[0065] S3.2. Weigh 5.299 g of Na2CO3 (500 mmol) using weighing paper and place it in a 50 ml beaker. Dissolve it in a small amount of water and transfer it to a 50 ml volumetric flask to make a 1 mol / L solution B.

[0066] S3.3. Use a pipette to transfer 20 ml of solution A and 16 ml of solution B into a 100 ml beaker and stir vigorously for 0.5 h. Transfer the stirred liquid to a 50 ml reactor and react at 150°C for 15 h. When cooled to room temperature, centrifuge and wash the product by washing it three times with deionized water and three times with anhydrous ethanol at a speed of 4000 rad / min. Then dry it at 80°C to obtain a powdered nickel-cobalt-iron LDH catalyst.

[0067] Preparation of S4 and NiCoFe / NSC bifunctional catalysts

[0068] S4.1 Take 0.5 g of nitrogen-sulfur doped graphene coconut shell carbon in S2.3 and 0.5 g of nickel-cobalt-iron LDH catalyst in S3.2 in a ratio of 1:1 and mix them in ultrapure water. Ultrasonicate for 2 h at room temperature with an ultrasonic power of 230 W. Centrifuge and wash them. The centrifugal washing is to wash them 3 times with deionized water and 3 times with anhydrous ethanol. The speed of centrifugal washing is 4000 rad / min. Then, dry them at 80 ° C to obtain coconut shell carbon transition metal bifunctional catalyst (nitrogen-sulfur doped graphene coconut shell carbon loaded nickel-cobalt-iron LDH bifunctional catalyst, denoted as Ni 0.1 Co 0.4 Fe 0.5 / NSC bifunctional catalyst).

[0069] Example 3

[0070] A method for preparing a coconut shell carbon transition metal bifunctional catalyst comprises the following steps:

[0071] S1. Preparation of graphene-coconut shell carbon

[0072] S1.1. Collect enough coconut shells, remove the coconut meat, crush the coconut shells into pieces, dry them at 80°C for 24 hours, crush the dried coconut shells, and sieve them to obtain particles with a 100-mesh sieve;

[0073] S1.2. Place the pellets prepared in S1.1 into a tube furnace and carbonize them at 600°C in an argon atmosphere for 2.5 h to obtain a preliminary coconut shell carbon sample.

[0074] S1.3. Stir 5 g of coconut shell carbon with 115 ml of concentrated sulfuric acid in an ice-water bath. Add potassium permanganate until the solution turns brown. Remove the ice-water bath and incubate in a water bath at 35 ± 5 °C for 8 h.

[0075] S1.4. Add 750 ml of deionized water intermittently and stir for 10 minutes. Then add 25 ml of hydrogen peroxide and stir until the solution turns light golden yellow.

[0076] S1.5. The solution in S1.4 was allowed to stand for 10 h, the supernatant was removed, and 200 ml of 5 wt% hydrochloric acid solution was added, mixed evenly, and centrifuged. After centrifugation, the supernatant was removed and an appropriate amount of deionized water was added for washing. After repeated several times, the remaining solution was poured into a Petri dish and frozen at -20°C for 5 h. The sample was then transferred to a freeze drying oven at -45°C and freeze-dried for 42 h to obtain a graphene-type coconut shell carbon sample.

[0077] S2, Graphene-based Coconut Shell Carbon Doped with Nitrogen and Sulfur

[0078] S2.1. Ultrasonic dispersion of 0.1 g of graphene-coconut shell carbon in 500 ml of 98 vol% ethanol. Add 0.5 g of hydrophilic nano-SiO2 (15 nm) and sonicate thoroughly. Then, remove the ethanol by rotary evaporation at atmospheric pressure (80°C) and 0.09 MPa (55°C) to obtain a flaky solid, which is then dried in an oven at 80°C.

[0079] S2.2. Mix 0.6 g of the flaky solid obtained in S2.1 with 0.5 g of melamine and 0.5 g of dibenzyl disulfide, and grind them. Place the resulting mixture in a tube furnace and heat it to 300°C under a nitrogen atmosphere, hold for 10 min, then heat it to 900°C and heat at 900°C for 1 h at a heating rate of 5°C / min.

[0080] S2.3. Soak the product obtained after heating in S2.2 in 50 mL of hydrofluoric acid for 36 h to remove silica, and then centrifuge to remove residual hydrofluoric acid. The centrifugal washing is performed by first washing with deionized water three times and then washing with anhydrous ethanol three times at a speed of 3000 rad / min. The obtained product is placed in a vacuum drying oven and dried at 80°C for 12 h to obtain nitrogen-sulfur doped graphene coconut shell carbon;

[0081] S3. Hydrothermal preparation of nickel-cobalt-iron LDH catalyst

[0082] S3.1. Mix nickel chloride, cobalt chloride, and ferric chloride in a molar ratio of 1:8:1 (8 mmol total) in a 50 ml beaker. Dissolve in 20 ml of ultrapure water to prepare a 0.4 mol / L mixed metal solution A.

[0083] S3.2. Weigh 5.299 g of Na2CO3 (500 mmol) using weighing paper and place it in a 50 ml beaker. Dissolve it in a small amount of water and transfer it to a 50 ml volumetric flask to make a 1 mol / L solution B.

[0084] S3.3. Use a pipette to transfer 20 ml of solution A and 16 ml of solution B into a 100 ml beaker and stir vigorously for 0.5 hours. Transfer the stirred liquid to a 50 ml reactor and react at 100°C for 20 hours. When cooled to room temperature, centrifuge and wash the product by washing it three times with deionized water and three times with anhydrous ethanol at a speed of 4000 rad / min. Then dry it at 80°C to obtain a powdered nickel-cobalt-iron LDH catalyst.

[0085] Preparation of S4 and NiCoFe / NSC bifunctional catalysts

[0086] S4.1 Take 0.5 g of nitrogen-sulfur doped graphene coconut shell carbon in S2.3 and 0.5 g of nickel-cobalt-iron LDH catalyst in S3.2 in a ratio of 1:1 and mix them in ultrapure water. Ultrasonicate for 2 h at room temperature with an ultrasonic power of 230 W. Centrifuge and wash them. The centrifugal washing is to wash them 3 times with deionized water and 3 times with anhydrous ethanol. The speed of centrifugal washing is 4000 rad / min. Then, dry them at 80 ° C to obtain coconut shell carbon transition metal bifunctional catalyst (nitrogen-sulfur doped graphene coconut shell carbon loaded nickel-cobalt-iron LDH bifunctional catalyst, denoted as Ni 0.1 Co 0.8 Fe 0.1 / NSC bifunctional catalyst).

[0087] Comparative Example 1

[0088] The difference between this comparative example and Example 1 is that the coconut shell carbon is not doped with nitrogen and sulfur, and step S2 and the graphene coconut shell carbon doped with nitrogen and sulfur are omitted. The other steps are the same as those in Example 1. The target product obtained is Ni 0.1 Co 0.6 Fe 0.3 / C.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 1 is that the molar ratio of nickel chloride, cobalt chloride and ferric chloride in step S3.1 is 1:3:6, and the other steps are the same as in Example 1. The target product obtained is Ni 0.1 Co 0.3 Fe 0.6 / NSC.

[0091] Experimental Example 1 OER electrochemical testing of materials using a three-electrode system

[0092] Coconut shell carbon transition metal bifunctional catalyst (nitrogen and sulfur doped graphene coconut shell carbon supported nickel cobalt iron LDH bifunctional catalyst Ni 0.1 Co 0.6 Fe 0.3 / NSC、Ni0.1 Co 0.4 Fe 0.5 / NSC、Ni 0.1 Co 0.8 Fe 0.1 / NSC) and Ni prepared in Comparative Examples 1 and 2 0.1 Co 0.6 Fe 0.3 / C、Ni 0.1 Co 0.3 Fe 0.6 The NSC / SSC catalysts were tested on a CHI760E electrochemical workstation at 25°C. 5 mg of the catalyst, 1425 μL of anhydrous ethanol, and 75 μL of a 5 wt% Nafion solution were slurried and ultrasonicated for over 30 minutes to form a homogeneous mixture. 20 μL of the mixture was then dripped onto an L-shaped glassy carbon electrode for testing. A three-electrode system was formed, using the L-shaped glassy carbon electrode as the working electrode, a platinum wire electrode as the counter electrode, and a mercury / mercury oxide (Hg / HgO) electrode as the reference electrode. Testing was performed in 1 M KOH electrolyte. The results are shown in Table 1.

[0093] Table 1 Electrochemical test results

[0094] <![CDATA[10mA / cm 2 Overpotential Example 1 289 Example 2 306 Example 3 300 Comparative Example 1 290 Comparative Example 2 329

[0095] The results in Table 1 show that the coconut shell carbon transition metal bifunctional catalysts (nitrogen-sulfur doped graphene coconut shell carbon supported nickel-cobalt-iron LDH bifunctional catalysts) prepared in Examples 1-3 of the present invention have good OER activity, and their OER polarization curves are shown in FIG. Figure 1 The OER activity of the catalyst prepared in Comparative Example 2 is lower than that in Example 1. This is because when the Fe content exceeds 50%, the LDH (layered double hydroxide) structure cannot be formed according to scanning electron microscopy. The interlayer anions of the LDH structure are conducive to the OER reaction and the improvement of activity.

[0096] Experimental Example 2 ORR electrochemical test of materials using a three-electrode system

[0097] Coconut shell carbon transition metal bifunctional catalyst (nitrogen and sulfur doped graphene coconut shell carbon supported nickel cobalt iron LDH bifunctional catalyst Ni 0.1 Co 0.6 Fe 0.3 / NSC、Ni 0.1 Co 0.4 Fe 0.5 / NSC、Ni 0.1 Co 0.8 Fe 0.1 / NSC) and Ni prepared in Comparative Examples 1 and 2 0.1 Co 0.6Fe 0.3 / C、Ni 0.1 Co 0.3 Fe 0.6 The NSC / NSC catalysts were tested on a CHI760E electrochemical workstation at 25°C. 5 mg of the catalyst, 1425 μL of anhydrous ethanol, and 75 μL of a 5 wt% Nafion solution were slurried and sonicated for over 30 minutes to form a homogeneous mixture. 20 μL of the mixture was then dripped onto a disk electrode for testing. A three-electrode system was formed, with the disk electrode serving as the working electrode, a platinum wire electrode as the counter electrode, and a mercury / mercury oxide (Hg / HgO) electrode as the reference electrode. Testing was performed in 0.1 M KOH electrolyte. The results are shown in Table 2.

[0098] Table 2 Electrochemical test results

[0099] Half-wave potential mV <![CDATA[Limiting current density mA / cm 2 > Example 1 0.811 -4.9735 Example 2 0.787 -4.3042 Example 3 0.735 -3.7615 Comparative Example 1 0.729 -3.5016 Comparative Example 2 0.802 -4.8652

[0100] As shown in Table 2, the coconut shell carbon transition metal bifunctional catalysts (nitrogen-sulfur doped graphene coconut shell carbon supported nickel-cobalt-iron LDH bifunctional catalysts) prepared in Examples 1-3 of the present invention have good ORR activity. The ORR polarization curves of the bifunctional catalysts prepared in Examples 1-3 of the present invention and Comparative Example 1 are shown in Figure 2. Figure 2 As shown in the figure, the ORR activity of the catalyst prepared in Example 1 is significantly improved compared with that in Comparative Example 1 (coconut shell carbon not doped with nitrogen and sulfur). This is because the highly electronegative N atoms can induce electron transfer of C atoms, thereby improving the adsorption capacity and conductivity of the graphene coconut shell carbon, while S doping can produce an uneven spin density distribution to adjust the electronic structure. Under the combined action of N and S, the ORR catalytic activity of the coconut shell carbon is improved.

[0101] Test Example 3 Catalyst zinc-air battery performance test

[0102] The coconut shell carbon transition metal bifunctional catalyst prepared in Example 1 (nitrogen-sulfur doped graphene coconut shell carbon supported nickel-cobalt-iron LDH bifunctional catalyst Ni 0.1 Co 0.6 Fe 0.3 / NSC) were used in zinc-air batteries (ZABs) for practical application testing. The zinc sheet served as the anode of the battery, the cathode was the air electrode (diaphragm, nickel foam, carbon paper coated with catalyst and air diffusion layer), and the electrolyte was a mixed aqueous solution of 6M KOH and 0.2M Zn(OAc)2.

[0103] The results are as follows Figure 3 As shown, the coconut shell carbon transition metal bifunctional catalyst prepared in Example 1 (nitrogen-sulfur doped graphene coconut shell carbon supported nickel-cobalt-iron LDH bifunctional catalyst Ni 0.1 Co 0.6 Fe0.3 / NSC) assembled into a zinc-air battery at 10 mA cm -2 At a current density of 1.5 GHz, zinc-air batteries have excellent charge-discharge cycle stability.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a coconut shell carbon transition metal bifunctional catalyst, characterized in that: The following steps are involved: S1. Preparation of graphene coconut shell carbon Carbonize the coconut shell, mix it with concentrated sulfuric acid in an ice water bath, add potassium permanganate until the solution turns brown, react in a water bath at 30-40°C, add hydrogen peroxide until the solution turns light golden yellow, let it stand, remove the supernatant, add hydrochloric acid solution and mix well, centrifuge, remove the supernatant, wash, and freeze-dry to obtain graphene coconut shell carbon; S2, Graphene-based Coconut Shell Carbon Doped with Nitrogen and Sulfur The graphene coconut shell carbon is dispersed in a solvent, silicon dioxide is added, ultrasonicated, the solvent is removed to obtain a solid, the solid is mixed and ground with a nitrogen-containing compound and a sulfur-containing compound, calcined under an inert gas atmosphere, immersed in a strong acid, centrifuged and washed, and dried to obtain nitrogen-sulfur doped graphene coconut shell carbon; S3, Hydrothermal preparation of Ni-Co-Fe LDH catalyst Mix nickel chloride, cobalt chloride, ferric chloride and water to obtain a metal solution A; mix sodium carbonate and water to obtain an alkaline solution B; mix A and B evenly, react at 100-150° C. for 15-20 hours, cool, centrifuge, wash, and dry to obtain a nickel-cobalt-iron LDH catalyst; Preparation of S4 and NiCoFe / NSC bifunctional catalysts The nitrogen-sulfur doped graphene coconut shell carbon in S2 and the nickel-cobalt-iron LDH catalyst in S3 were mixed in water, ultrasonicated, centrifugally cleaned, and dried to obtain a coconut shell carbon transition metal bifunctional catalyst, recorded as NiCoFe / NSC.

2. The method for preparing a coconut shell carbon transition metal bifunctional catalyst according to claim 1, characterized in that: The molar ratio of nickel chloride, cobalt chloride and ferric chloride in the S3 is 1:4-8:1-5; the molar number of Fe accounts for less than 50% of the total molar number of Ni, Co and Fe.

3. The method for preparing a coconut shell carbon transition metal bifunctional catalyst according to claim 1, characterized in that: The coconut shell carbonization in S1 is specifically to dry the coconut shell, crush it, and place it in a tubular furnace for carbonization under an argon atmosphere at 600°C; the concentration of the hydrochloric acid solution is 5wt%; the freeze-drying is specifically to first freeze it at -5 to -20°C for 5-8h, and then freeze-dry it at -60 to -45°C for 36-42h.

4. The method for preparing a coconut shell carbon transition metal bifunctional catalyst according to claim 1, characterized in that: The solvent in S2 is 98-99.8 vol% ethanol, and the silica is hydrophilic nano-silica; the mass ratio of the graphene coconut shell carbon to the hydrophilic nano-silica is 1:5; the method for removing the solvent is to perform secondary rotary evaporation under normal pressure and low pressure conditions, the normal pressure rotary evaporation temperature is 70-80°C, the low pressure is 0.09 MPa, and the low pressure rotary evaporation temperature is 55-60°C; the strong acid is hydrofluoric acid.

5. The method for preparing a coconut shell carbon transition metal bifunctional catalyst according to claim 1, characterized in that: The inert gas in S2 is nitrogen, the nitrogen-containing compound is melamine, and the sulfur-containing compound is dibenzyl disulfide; the molar ratio of the solid, melamine, and dibenzyl disulfide is 6:5:5; the tubular furnace is heated to 300°C, maintained for 10 minutes, then heated to 900°C, and heated at 900°C for 1 hour, and the heating rate is 5°C / min.

6. The method for preparing a coconut shell carbon transition metal bifunctional catalyst according to claim 1, characterized in that: The centrifugal washing is firstly washed with deionized water for 2 to 4 times, and then washed with anhydrous ethanol for 2 to 4 times, and the rotation speed of the centrifugal washing is 3000-4000 rad / min.

7. The method for preparing a coconut shell carbon transition metal bifunctional catalyst according to claim 1, characterized in that: The mass ratio of nitrogen-sulfur doped graphene coconut shell carbon to nickel-cobalt-iron LDH catalyst in S4 is 1:

1.

8. A coconut shell carbon transition metal bifunctional catalyst, characterized in that: The catalyst is prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the coconut shell carbon transition metal bifunctional catalyst prepared by any one of the preparation methods of claims 1 to 7 in zinc-air batteries.

10. A zinc-air battery, characterized in that: The anode is a zinc sheet, and the cathode is an air electrode. The air electrode comprises a diaphragm, nickel foam, carbon paper coated with a coconut shell carbon transition metal bifunctional catalyst prepared by any one of claims 1 to 7, and an air diffusion layer.

Citation Information

Patent Citations

  • Biomass carbon catalyst and preparation method and application thereof

    CN105375042A

  • Nitrogen-doped carbon material support multi-metal catalyst as well as preparation method and application thereof

    CN108187716A

  • Nickel-cobalt-iron tri-metal catalyst through phosphating and then vulcanizing of in situ grown graphene and preparation method of nickel-cobalt-iron tri-metal catalyst

    CN113430533A

Cited By

  • Zinc air battery catalyst and preparation method thereof

    CN120473512A